STRATEGI PENGEMBANGAN PARIWISATA BUDAYA LOKAL STUDI DI DINAS BUDPAR KEPEMUDAAN DAN OLAH RAGA DI KABUPATEN BARITO UTARA: STRATEGI PENGEMBANGAN PARIWISATA BUDAYA LOKAL STUDI DI DINAS BUDPAR KEPEMUDAAN DAN OLAH RAGA DI KABUPATEN BARITO UTARA - Jaya, Imanuel (Journal Ilmu Sosial, Politik, dan Ilmu Pemerintahan, 2020)
This research was conducted to find out how the strategy of developing local cultural tourism, which is where researchers choose the location of research in the Department ofCulture, Tourism, Youth and Sports. And analyze the factors that influence the strategy of developing local cultural tourism in North Barito Regency. The purpose of this study is to describe and analyze how the local culture tourism development strategy in North Barito Regency, the theory used by researchers using the theory of Cooper, Fletcher, Gilberth, Shepherd and Wanhill (1998) which became the main elements in tourism development strategies, namely Objects and Attraction, Accessibility, Amenities, Supporting Facilities, and Institutions. This study uses descriptive qualitative research methods. Data taken based on information from informants at the elemental level of the Head of the Office of Culture, Tourism, Youth and Sports, Secretary of the Office of Culture, Tourism, Youth and Sports, Secretary of the Department of Culture, Tourism, Youth and Sports, and Society, and data obtained through the results of research in the field. Data collection techniques in the form of observation, interviews and literature. The result showed that Strategy for the development of Local Culture Tourism in North Barito District did not go well. Because it is still lacking in several factors such as lodging facilities, and ATM at the location of tourist attractions is still not available, and community involvement in tourism development is still minimal. The factors that influence the development of tourism in North Barito Regency are two factors, namely supporting factors: There is cooperation between institutions or other institutions in tourism development. Inhibiting factors in tourism development in North Barito Regency are: Sources of funding in development that are still lacking or inadequate, lack of community involvement in tourism activities, and HR factors that work are still not optimal so performance un development is slow to run.